Increasing markets and decreasing package weight for high-specific-power photovoltaics. (November 2018) - Reese, Matthew; Glynn, Stephen; Kempe, Michael; McGott, Deborah; Dabney, Matthew; Barnes, Teresa; Booth, Samuel; Feldman, David; Haegel, Nancy
Abstract Thin-film and emerging technologies in photovoltaics (PV) offer advantages for lightweight, flexible power over the rigid silicon panels that dominate the present market. One important advantage is high specific power (the power-to-weight ratio). Here we consider niche market size, price points and value propositions that can provide a path for new PV market entrants. Examining the cost–production experience curves of Si, CdTe and CIGS PV suggests that a minimum market size of US0.2–1 billion is required to incubate a new market entrant. Several markets requiring high specific power meet this threshold. We assess the critical role of the substrate, packaging and interconnects and provide a quantitative assessment of pathways to maximize specific power. With all requisite components included, along with requirements for safety and reliability, we estimate a lower bound for a durable lightweight module at about 300–500 g m−2 . Pairing this bound with a 15%-efficiency thin-film or 35%-efficiency III–V module would yield specific powers up to 500 W kg−1 or 1, 167 W kg−1, respectively. Although rigid silicon panels dominate the solar power market, they are unsuitable for niche applications such as portable charging or drones, where thin-film and flexible technologies would be advantageous. This Analysis examines the needs of niche markets and the packaging weights that would be required to enable such photovoltaic devices to enter them.